2005
DOI: 10.1017/s0025315405012142
|View full text |Cite
|
Sign up to set email alerts
|

migratory behaviour of the thornback ray, raja clavata, in the southern north sea

Abstract: although depleted throughout the european continental shelf, the relatively high density of thornback rays raja clavata, in the thames estuary (uk) makes it an important stock centre and potential focus for species management. to describe spatial and temporal distribution, 197 thornback rays were tagged with electronic data storage tags (dsts) and released in the thames estuary in october 1999 and 2000, and 100 rays tagged with conventional tags in 2000. fifty-one per cent of dsts and 48% of conventional tags … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
2
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 18 publications
4
71
2
6
Order By: Relevance
“…Indeed globally, the number of skates and rays landed has been higher than landings of sharks since about 1975, suggesting skate populations may be at greater risk of overexploitation than in prior decades (Field et al 2009, Dulvy et al 2014. Previous research into species distributions and habitat preferences in the Rajidae is sparse and has relied principally on trawl data, either from fisheries (Serra-Pereira et al 2014), or from fishery independent surveys (Compagno et al 1991, Dulvy et al 2000, Hunter et al 2005b, Hunter et al 2006, Compagno & Ebert 2007, Maravelias et al 2012, Martin et al 2012. Studies such as these are typically very large scale and lack information about fine scale movements and behaviours which can significantly affect species interactions and distributions (Hussey et al 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed globally, the number of skates and rays landed has been higher than landings of sharks since about 1975, suggesting skate populations may be at greater risk of overexploitation than in prior decades (Field et al 2009, Dulvy et al 2014. Previous research into species distributions and habitat preferences in the Rajidae is sparse and has relied principally on trawl data, either from fisheries (Serra-Pereira et al 2014), or from fishery independent surveys (Compagno et al 1991, Dulvy et al 2000, Hunter et al 2005b, Hunter et al 2006, Compagno & Ebert 2007, Maravelias et al 2012, Martin et al 2012. Studies such as these are typically very large scale and lack information about fine scale movements and behaviours which can significantly affect species interactions and distributions (Hussey et al 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…Tagging studies (mark/recapture) conducted for Rajidae species have indicated traveling distances on the order of hundreds of kilometers, (Templeman 1984;Walker et al 1997;Hunter et al 2005) as compared to traveling distances on the order of thousands of kilometers for many bony and cartilaginous fishes Queiroz et al 2005) supporting the hypothesis of regional population structure in A. radiata. A closer look within the Rajidae, however, reveals that A. radiata travels the farthest-between 1.4 and 3 times as far as R. clavata (Templeman 1984;Walker et al 1997).…”
Section: Population Differentiationmentioning
confidence: 96%
“…), to attach acoustic tags and DSTs. A common method has been to attach a loose-hanging tether from the electronic tag to a wire saddle through the dorso-lateral musculature, secured by a Peterson disc on the other side, for species such as Atlantic cod (Gadus morhua) and plaice (Pleuronectes platessa) [49,50] or through fin musculature for thornback ray (Raja clavata) [51]. The purpose of the Peterson tag is to spread the tension and reduce cutting of the wire through the skin and muscle.…”
Section: Cebidichthys Violaceusmentioning
confidence: 99%